Optimizing smart grids with blockchain-driven automation and demand response - Jyothi, B.; Pabbuleti, Bhavana; Ponnala, Ravi; Rao, Kambhampati Venkata Govardhan; Srilakshmi, S. Sai; Narasimha, Putta Dhanush; Yadav, Mareboyina Karthik; Kumar, Malligunta Kiran; Reddy, Ch. Rami (Institute of Advanced Engineering and Science, 2025)
To increase resilience, efficiency, and engagement in the network, it shall develop and test its smart grid system integrating blockchain-based authentication and automated demand response management. Simulations are made on the dynamic behavior of the grid in energy generation, consumption, and management through demand responses through MATLAB/Simulink assessment of performance and stability. Ethereum is used in implementing and managing smart contracts that automate and secure events of demand response and consumer interactions for transparency in transactions. It uses Python with Pandas to process, analyze, and visualize simulation data that gives insight into the effectiveness of demand response strategies; PostgreSQL supports the structured storage and querying of data with comprehensive data management. Proper integration of such tools can result in the proper robust simulation of the smart grid system that is highly reliable, efficient usage of energy, and can empower consumers through secure, efficient demand response mechanisms. These immediate issues about managing the grid can thus solve the way toward the future development of such smart grid technologies and their possible integration with the blockchain.